Review article. Laura Wright, Sunnyside – A Sociolinguistic History of British House Names (Oxford: Oxford University Press for The British Academy, 2020). 295 pp. £65. ISBN: 9780197266557. (2021) - Patterson, William M. H.
No abstract available